Pendidikan Berorientasi fi Al-Dunya Hasanah wa fi Al-Akhirah Hasanaha: Menggali Pemikiran al-Ghazali di dalam Kitab Ayyuha al-Walad - Rahem, Zaitur (JURNAL AT-TURAS, 2017)
Indonesia's education world has never been separated from slashing humanitarian issues. In Madura, precisely in Sampang district, a student allegedly persecuted his teacher to death. This event is a sad story in our education world. Concept structures, teaching materials, and procedures in the organs of the world of education require reformation. One of them is to excite insightful and good-oriented education in the world and in the hereafter. Imam Al-Ghazali's thoughts in the form of synergy over knowledge, charity, and the position of ulama became a concept offer to answer the problem of the homeland education